Determination of Compatibility of Polymer Systems and Study of Chemical Properties of their Mixtures - Shixaliyev Kerem Sefi* (International Journal of Cheminformatics, 2026)
We have obtained mechanical strength of materials as a result not by synthesizing new polymers, but by using industrial polymers. We have developed a technology for obtaining new composite materials based on industrial multi-tonnage polymers of high-strength polyethylene (HSPE), polyvinyl chloride (PVC), polyurethane thermoplastic elastomer (DUTEP), butyl rubber (BR), chlorocarboxylate polyethylene (CCPE), ethylene propylene rubber (EPR). To obtain a composition from these polymers, their mixture compatibility was first determined using the most modern methods. Thermodynamic compatibility of the butyl rubber-polyethylene (BR-LDPE), polyvinyl chloride, HSPE, polyurethane thermoplastic elastomer, PVC-chlorocarboxylate polyethylene (CPE), (CREP-VC) systems was studied using inverse gas chromatography methods, and structural features of these systems were revealed using IR spectroscopy and polarization microscopy. The study demonstrated that the incorporation of polyfunctional groups such as chlorine, hydroxyl, and carboxyl markedly influences the compatibility mechanism and provides a consistent set of enhanced properties, including improved adhesive performance, greater tensile and tear strength, and increased resistance to thermal and chemical degradation. These improvements arise from intermolecular polar interactions between macromolecular chains. The solubility parameters of four polymers with varying degrees of polarity were evaluated using turbidimetric titration (TDT) and inverse gas chromatography techniques. Based on the temperature dependence of the solubility parameter derived from sorbent retention times, the parameter value normalized to 25 °C was calculated and compared with that obtained through the TDG method at the same temperature. The results indicated that the discrepancy between the solubility parameters determined by the two methods increased with higher polymer polarity. This phenomenon is attributed to the fundamentally different states of the examined polymer–solvent systems.
Keywords: Stability; butyl rubber (BR); chlorocarboxylate polyethylene (CCPE); compatibility; ethylene propylene rubber (EPR). solubility parameter; high-strength polyethylene (HSPE); macromolecules; polyfunctional groups; polymer; polyurethane thermoplastic elastomer (PUTE); polyvinyl chloride (PVC); sorbent